Uneven winter snow influence on tree growth across temperate China. (6th November 2018) - Wu, Xiuchen; Li, Xiaoyan; Liu, Hongyan; Ciais, Philippe; Li, Yuanqiao; Xu, Chongyang; Babst, Flurin; Guo, Weichao; Hao, Bingyan; Wang, Pei; Huang, Yongmei; Liu, Shaomin; et al.
Abstract: Winter snow is an important driver of tree growth in regions where growing‐season precipitation is limited. However, observational evidence of this influence at larger spatial scales and across diverse bioclimatic regions is lacking. Here, we investigated the interannual effects of winter (here defined as previous October to current February) snow depth on tree growth across temperate China over the period of 1961–2015, using a regional network of tree ring records, in situ daily snow depth observations, and gridded climate data. We report uneven effects of winter snow depth on subsequent growing‐season tree growth across temperate China. There shows little effect on tree growth in drier regions that we attribute mainly to limited snow accumulation during winter. By contrast, winter snow exerts important positive influence on tree growth in stands with high winter snow accumulation (e.g., in parts of cold arid regions). The magnitude of this effect depends on the proportion of winter snow to pre‐growing‐season (previous October to current April) precipitation. We further observed that tree growth in drier regions tends to be increasingly limited by warmer growing‐season temperature and early growing‐season water availability. No compensatory effect of winter snow on the intensifying drought limitation of tree growth was observed across temperate China. Our findings point toward an increase in drought vulnerability of temperate forests in a warming climate. Abstract : Winter snow exerts little effect on tree growth in drier regions attributed to limited snow accumulation during winter. We further found that there was no compensatory effect of winter snow on the intensifying drought limitation of tree growth across temperate China.